G532 Pilot diabetes formal social education with the hospital school. (27th April 2016) - Jain, N; Dublon, V; Clair, B; Green, S; Freeman, E
Abstract : Context: A multidisciplinary Diabetes Education Afternoon was held at a Hospital School for children with diabetes aged 10–12 yrs. The team included the deputy head teacher, play therapists, diabetes team (consultants, dietician) and a junior paediatric trainee. Problem: The National Diabetes Service Improvement Delivery Plan 2013–2018 highlighted that there was need and desire by patients, families and practitioners for self-directed management through structured patient education programmes. In particular the transition from primary to secondary school is an especially difficult change where they undergo significant biopyschosocial changes and are expected to understand and self-manage greater aspects of their diabetes. Assessment of problem and analysis of its causes: In a meeting with the diabetes team we found that whilst we deliver education through annual review clinics and one-to-one sessions, there is no formal social educational programme. There are 12 children between 8–12 yrs with diabetes looked after by the team. Subsequently we approached the School and play therapists to discuss the issue and design a joint educational afternoon. Intervention: 4 stations, each lasting 20 mins: Apps and other resources: Uploaded on an iPad. Used to make insulin calculations. Know your carbs: Using food models to divide food into carbohydrates and non-carbohydrates. Conquering Labels: Interpreting nutritional labels on food. Food Kitchen: Measuring and estimating carbohydrate foodstuffs. 5 mins presentation from Diabetes UK. (Figure 1 ) Study design: qualitative Strategy for change: Using the Model for Improvement, the first PDSA cycle tested the training with children at the school. We then adapted it in response to the feedback from participants. A revised lesson plan was made and used in our second cycle. We invited 6 patients with diabetes, aged between 10–11 years, and their families on an afternoon during school holidays. The whole multidiscipplinary team was involved on the day. Measurement of improvement: The children and their parents filled in pre- and post- session feedback forms. These were followed by telephone interviews a week later. Effects of changes: There was measurable improvement in the children's confidence and knowledge of their own insulin: carbohydrate, identifying and measuring carbohydrates as well as calculating their insulin requirements (INSERT Graph). Interviews a week later revealed that more children were self-managing their insulin calculations. Parents felt that the session was empowering for themselves and their children. All highlighted they liked the opportunity to meet other families with children with diabetes and that it was beneficial for the siblings (INSERT Diagram). We are now in discussion with our colleagues leading diabetes services in the region with a view to organise regular education training events in the local community. The main challenges encountered were the session running over time and that parents felt they would like more time for interaction with eachother. Lessons learnt: We learnt that public health education for children, especially for diabetes, is greatly improved by having a multidisciplinary approach; particularly input from the School, play therapists and patients was invaluable. We were surprised at how engaged the school teachers and play therapists were in the process and their expertise allowed us to deliver a session in a non-hospital setting with a team who had an excellent understanding of the information we wished to disseminate at a level that was appropriate for their specific ages in an interactive, friendly and relaxed atmosphere. Next time we will limit the session to 2 hrs after readjusting the timings and content, as well as having a seperate, paralell session for parents. Message for others: Sessions like these can provide an excellent forum for both parents and children to improve their knowledge, discuss difficulties they are facing and facilitate the development of local diabetes social networks.